Temperature of the active layer in the forest-tundra zone in the north of Western Siberia (Pangody) forest-tundra zone in the north of Western Siberia - Oleg, Sizov; Soromotin Andrey; Brodt Leya (Zenodo, 2020)
Temperature of the active layer in the forest-tundra zone in the north of Western Siberia (Pangody) forest-tundra zone in the north of Western Siberia (7 sites). Temperature was measured with a Tr 46908 thermometer (TR di Turoni & c. Snc, Italy) and drilling was carried out using a hand-held motor-drill Stihl BT 360 (Stihl, Germany). Date of field investigations - 16 and 17 August 2020.